2022
DOI: 10.55446/ije.2021.305
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Insecticides and Biopesticides Against Major Sucking Insect Pests of Indian Bean <i>Lablab Purpureus</i> Var. <i>Typicus</i>

Abstract: This study was conducted to evaluate the efficacy of some insecticides and biopesticides against aphid Aphis craccivora (Koch), leafhopper Empoasca fabae (Harris) and whitefly Bemisia tabaci (Genn.) on Indian bean during kharif, 2019 at the SKN College of Agriculture, Jobner, Jaipur. On the basis of reduction in incidence, spiromesifen 22.9SC, diafenthiuron 50WP and standard check (alternate spray of dimethoate 30EC and malathion 50 EC) were observed to be the most effective. The pyriproxyfen 10.8EC, emamectin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
1
0
Order By: Relevance
“…Shakya et al (2020) [6] revealed that diafenthiuron 50 WP @ 312.5 g a.i./ha was found the most effective against whitefly in mung bean at Ayodhya, Uttar Pradesh. Contrary to the present results, Choudhary et al (2022) [1] found that diafenthiuron 50 WP and chlorantraniliprole 18.5 SC were most effective against aphid and leafhopper population infesting indian beans at Jobner, Rajasthan. The variations in effectiveness of these insecticides might be due to different doses, climatic conditions of the location, pest species or variations in crop.…”
Section: Pooled Over Yearscontrasting
confidence: 99%
“…Shakya et al (2020) [6] revealed that diafenthiuron 50 WP @ 312.5 g a.i./ha was found the most effective against whitefly in mung bean at Ayodhya, Uttar Pradesh. Contrary to the present results, Choudhary et al (2022) [1] found that diafenthiuron 50 WP and chlorantraniliprole 18.5 SC were most effective against aphid and leafhopper population infesting indian beans at Jobner, Rajasthan. The variations in effectiveness of these insecticides might be due to different doses, climatic conditions of the location, pest species or variations in crop.…”
Section: Pooled Over Yearscontrasting
confidence: 99%
“…P y m e t r o z i n e , 4 , 5 -d i h y d r o -6 -m e t h y l -4 -[ ( 3pyridylmethylene)-amino]-1,2,4-triazin-3(2H)-one (Figure 1), is a novel insecticide with effects on neuroregulation or nerve-muscle interaction against sucking insects by preventing these ones from inserting their stylus into the plant tissue, reduction in feeding and alteration in probing behaviors characterized by the prolonged non-probing, penetration initiation and extracellular activity and shortened salivation and phloem-related activities [1][2][3]. Pymetrozine has been widely used in rice against plant hoppers [4] as a substitution for highly toxic organophosphate pesticides and vegetables [5].…”
Section: Introductionmentioning
confidence: 99%